Antimicrobial Activity of Leaves and Flowers of Cassia auriculata linn (Bangladesh Journal of Scientific and Industrial Research, 2012)
Since ancient times plant as sources of medicinal compounds have continued to play a dominant role in the maintenance of human health. To treat chronic and infectious diseases plants used in traditional medicine contain a wide range of ingredients. In this regard, Cassia auriculata L. (Caesalpiniaceae) is widely used in Ayurvedic medicine as a tonic, astringent and as a remedy for diabetes, conjunctivitis, ulcers, leprosy, skin and liver diseases. The aim of present study was to evaluate the antimicrobial activity of ethanolic extract of Cassia auriculata leaves and flowers (CALE & CAFE). CALE and CAFE exhibited broad spectrum antimicrobial activity against standard strains of Staphylococcus aureus, Escherichia coli and Bacillus subtilis and exhibited no antifungal activity against standard strains of Candida albicans and Aspergillus niger. Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) was carried out for CALE and CAFE. The results obtained in the present study indicate that the CALE and CAFE can be a potential source of natural antimicrobial agents. Key words: Cassia auriculata; Antimicrobial activity; Agar well diffusion method. DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9600 BJSIR 2011; 46(4): 513-518